HUBUNGAN STANDAR KOMPETENSI DAN MOTIVASI TERHADAP KINERJA PETUGAS BRIEFING OFFICE DI MAKASSAR AIR TRAFFIC SERVICES CENTRE (MATSC) - ENDANG SUGIH ARTI (Langit Biru: Jurnal Ilmiah Aviasi, 2011)
Improved performance officer MATSC Briefing office also supported by the competency standards (both theory and skills practice skills) owned by the graduate program of study Aeronautical Information STPI Curug. In this case, STPI Curug as provider of Aeronautical Information graduacted should give serious attention to this variable. This means that an effort from the STPI to really make the planning, management, implementation and monitoring of education in order to achieve the goal of producing aviation worker that ready to work. Likewise, an increase in performance of Briefing Office Officer in MATSC due to high employee motivation, this should be a concern for the management of PT. Angkasa Pura I to pay attention to this variable. This means that the management should make greater efforts to motivate employees to increase their performance over longer so productivity increases.